Accurate Detection of Hepatitis B Virus G1896A Mutant by Developed Taqman‐ARMS Followed a Strict Control System. Issue 4 (13th May 2015) - Lu, Renfei; Shao, Jianguo; Zhou, Min; Zhang, Hongping; Wu, Yueping
Abstract : Background: Hepatitis B virus (HBV) G1896A mutation was associated with HBeAg seronegativity and hepatitis B related acute‐on‐chronic liver failure. In this study, we developed Taqman amplification refractory mutation system (Taqman‐ARMS) and established a strict control system to detect HBV G1896A mutant. Methods: HBV viral DNA was isolated from 60 patient serum samples, and full‐length HBV genome was cloned. Then, Taqman‐ARMS was used to detect HBV G1896A mutant. Results: The assay has the sensitivity of 1E+3 IU/ml G1896A template, and 0.1% weak population virus with G1896A could be found in mixtures. Total of all 60 clinical samples random collected were detected by Taqman‐ARMS, the results were consistent with those by DNA sequencing. Conclusion: The proposed Taqman‐ARMS real‐time PCR method for the detection of G1896A mutation of HBV was rapid, simple, sensitive, specific, and applicable in the clinical setting.